Analisis Kelayakan Penyajian Buku Teks Bahasa Indonesia Kelas XI Kurikulum 2013 Edisi Revisi 2017 - Ilya Zulfadilla; Feona Pramoda Wardhani; Fiamanillah; Hanifa Yuti Islamiyah; Pajriansyah; Muhammad Mukhlis (UIR Press, 2022)
Textbooks are textbooks in a particular field of study that are standard books, compiled by experts in that field for instructional purposes and purposes equipped with suitable means of teaching and easily understood by the wearers in school. In this study, one approach is used, namely qualitative approach. The feasibility of this presentation aims to find out the feasibility of the textbook and of course know how appropriate and effective the textbook is in the process. In the feasibility of this presentation there are also three indicators that need to be considered, such as from the technique of presentation, supporting presentation, as well as coherence and traceability of the flow of thought. The feasibility of this presentation aims to find out the feasibility of the textbook and of course know how appropriate and effective the textbook is in the learning process. This can be interpreted with the feasibility of useful presentation on the target level of learning carried out.